Length of labour using vaginal misoprostol or dinoprostone for induction at various gestational ages: A retrospective cohort study. Issue 1 (26th July 2022) - Boyd, Victoria E.; Mackeen, A. Dhanya; Young, Amanda J.; Johns, Alicia; Lewis, Meredith W.; Paglia, Michael J.
Abstract: Introduction: Induction of labour is a common procedure performed on labour and delivery. There are multiple ways to achieve cervical ripening, however, no studies have evaluated these methods based on a patient's gestational age. The goal of this study is to compare the length of labour at specific gestational ages in women being induced with either vaginal misoprostol or the dinoprostone insert. Methods: A retrospective cohort study of 3774 singleton pregnancies from 2009 to 2019 at a health system with tertiary care and community hospitals was conducted. The primary outcome was time to insertion of medication to time to vaginal delivery. Secondary outcomes included length of first and second stages of labour, length of rupture of membranes, mode of delivery, neonatal Apgar scores at 1 and 5 min and neonatal intensive care unit admission. A generalized linear model was utilised for continuous outcomes and a logistic regression model was used for binary outcomes. Results: Across all gestational ages, women who received vaginal misoprostol had a shorter labour course than women who received dinoprostone (in hours, preterm 18.2 vs. 26.3 p  < 0.01, term 15.9 vs. 24.4 p  < 0.01, late term 17.6 vs. 22.3 p  < 0.01). Patients that received misoprostol had a shorter first stage of labour (in hours, preterm 18.2 vs. 25.7 p  < 0.01, term 15.3 vs. 23.6 p  < 0.01, late term 16.5 vs. 21.1 p  < 0.01) and second stage of labour in the term and late term group (term 20.5 vs. 30.0 min. p  < 0.01, late term 30.0 vs. 47.0, p  = 0.05). Patients that received dinoprostone at term had higher odds of undergoing caesarean section (odds ratio (95% confidence interval): 1.34 (1.06, 1.70)). Conclusion: Patients that received vaginal misoprostol was associated with shorter labour course across all gestational ages. Patients that received dinoprostone at term had an increased risk of caesarean section.